Cluster farms in Mindanao are smallholder farmers' expectations being fulfilled? - Montiflor, Marilou O.; Batt, P.J.; Murray-Prior, Roy B. (2008)
Cluster farming means grouping farmers together to consolidate their produce to deliver in bulk, thus saving transportation and transaction costs. As this marketing strategy is an alternative to traditional vegetable marketing practices in the Philippines, there is a need to evaluate the extent to which cluster farming has fulfilled the farmers' expectations. The results demonstrate that even though farmers may not be financially better off, most of the cluster members' expectations had been met after joining the cluster.
Keywords: Cluster farming; Collaborative farming